Bilateral taurodontism in primary and permanent molars associated with hypodontia - Parmeshwarappa Poornima; Shashikant Katkade; Neena Indavara Eregowda; Kenchappanavar Maheshappa Sangeeta (Wolters Kluwer Medknow Publications, 2017)
The article is to present a case of bilateral taurodontism in primary and permanent molars associated with hypodontia and to discuss the endodontic aspects. Taurodontism in permanent molars are most commonly affected and it has a very low incidence, and very fewer cases are reported in the literature in the deciduous dentition. A 12-year-old boy presented with irregularly placed tooth in upper right back region of the jaw. Orthopantomogramrevealed taurodontism in seven teeth including both primary and permanent teeth, associated with congenitally missing three premolars and permanent mandibular central incisors. Taurodontism is more frequent in nonsyndromic familial tooth agenesis. Individuals in families with second premolar and molar oligodontia are more likely to have taurodontism. Since there is a wide variation in size and shape of pulp chamber with varying degree of obliteration and canal configuration, root canal therapy becomes a challenge so it is essential to recognize and render preventive care for these teeth.